2019
DOI: 10.2147/ott.s214881
|View full text |Cite|
|
Sign up to set email alerts
|

<p>SNHG8 is upregulated in esophageal squamous cell carcinoma and directly sponges microRNA-411 to increase oncogenicity by upregulating KPNA2</p>

Abstract: Background: The long noncoding RNA, small nucleolar RNA host gene 8 (SNHG8), is upregulated in multiple human cancer types. However, whether SNHG8 is aberrantly expressed in esophageal squamous cell carcinoma (ESCC) and its biological functions have yet to be elucidated. Thus, we aimed to determine the expression status of SNHG8 in ESCC, explore the effects of SNHG8 on the oncogenicity of ESCC, and investigate the potential underlying mechanisms. Methods: SNHG8 expression in ESCC tissues and cell lines was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Long non-coding RNA UCA1 can up-regulates PTP1B to enhance cell proliferation through sequestering miR-206 in breast cancer [38]. SNHG8 plays oncogenic roles in the malignancy of esophageal squamous cell carcinoma by sponging miR-411, thus increasing KPNA2 expression [39]. In this study, we identified two miRNAs (let-7b and miR-1266) binding with HOST2 and demonstrated a negative correlation between HOST2 expression and let-7b/miR-1266 in TNBC samples.…”
Section: Discussionmentioning
confidence: 66%
“…Long non-coding RNA UCA1 can up-regulates PTP1B to enhance cell proliferation through sequestering miR-206 in breast cancer [38]. SNHG8 plays oncogenic roles in the malignancy of esophageal squamous cell carcinoma by sponging miR-411, thus increasing KPNA2 expression [39]. In this study, we identified two miRNAs (let-7b and miR-1266) binding with HOST2 and demonstrated a negative correlation between HOST2 expression and let-7b/miR-1266 in TNBC samples.…”
Section: Discussionmentioning
confidence: 66%
“…The apoptosis of transfected cells was evaluated by menas of flow-cytometric analysis. 30 After cultivation for 48 h, transfected cells were harvested using trypsin without EDTA and rinsed with precooled phosphate-buffered saline, followed by quantification of apoptotic cells using the Annexin V-Fluorescein Isothiocyanate (FITC) Apoptosis Detection Kit (BioLegend, San Diego, CA, USA). Namely, the transfected cells were resuspended in 100 ÎŒL of Annexin-V-binding buffer prior to double staining with 5 ”L of Annexin V-FITC and 5 ”L of the propidium iodide solution.…”
Section: Flow-cytometric Analysis Of Apoptosismentioning
confidence: 99%
“…KPNA2, an adaptor protein for nuclear receptor importin-ÎČ, mediates numerous nuclear translocations of macromolecules by classical nuclear localization singal through the nuclear pore complex [25][26][27].…”
Section: Discussionmentioning
confidence: 99%